El rincón del arte para el desarrollo de la creatividad en niños y niñas de 4 a 5 años de edad de la unidad educativa Ángel Polibio Cháves”, provincia Bolívar, cantón Guaranda, periodo 2024. - Ninabanda Chela, Mariana Isabel (2025)
The research, titled "The Art Corner for the Development of Creativity in Children Ages 4 and 5 at the Ángel Polibio Cháves Educational Unit, Bolívar Province, Guaranda Canton, 2024 Period," explores the impact of using various games, activities, and materials on fostering children's creativity and imagination. The study highlights the importance of the art corner through the integration of diverse activities, in which children have the opportunity to express their ideas freely and spontaneously, developing skills and abilities. Creativity is considered a key aspect in the development of other fundamental elements for children's lives and futures. The study arose from pre-professional practice at the aforementioned educational institution, which motivated a deeper exploration of how to better utilize the art corner to enhance children's creativity. Therefore, it was conducted using a qualitative approach, supported by a detailed analysis that allowed for the development of viable research, supported by bibliographic studies presented within a theoretical framework. Data were collected through an interview with the teacher and direct observation of the children. The results were analyzed descriptively, demonstrating the positive influence of the art corner on children's creative development. Based on these findings, conclusions were drawn that contributed to the development of a teaching guide with activities aimed at strengthening creativity in children in early childhood education